2017
DOI: 10.18781/r.mex.fit.1708-3
|View full text |Cite
|
Sign up to set email alerts
|

Actividad antifúngica in vitro del aceite esencial de ajo (Allium sativum L.) contra Alternaria tenuissima

Abstract: Resumen. Los problemas ambientales generadospor el control químico de hongos fitopatógenos, requiere de la búsqueda de alternativas amigables con el medio ambiente para su control, como el aceite esencial de ajo (Allium sativum L.) para el control de Alternaria tenuissima. El objetivo del estudio fue caracterizar los volátiles del aceite esencial de ajo por cromatografía de gases acoplado a masas y evaluar el crecimiento radial y biomasa in vitro de A. tenuissima en presencia del aceite esencial. Se identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The inhibitory effect of garlic essential oil against A. parasiticus may be due to sulfur compounds. The essential oil used previously was analyzed by Muy-Rangel et al (2017) and report diallyl disulphide (23.64 %) and diallyl sulphide (20.33 %) in garlic essential oil (Sigma-Aldrich ® , lot MKBB8390V). These compounds of sulfur may interact with sulfhydryl groups of proteins (El-Sayed et al, 2017) in the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effect of garlic essential oil against A. parasiticus may be due to sulfur compounds. The essential oil used previously was analyzed by Muy-Rangel et al (2017) and report diallyl disulphide (23.64 %) and diallyl sulphide (20.33 %) in garlic essential oil (Sigma-Aldrich ® , lot MKBB8390V). These compounds of sulfur may interact with sulfhydryl groups of proteins (El-Sayed et al, 2017) in the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…For example, garlic (Allium sativa L.) is one plant used word-wide; it has volatile compounds with a broad antimicrobial spectrum (Benkeblia, 2004;Bayan et al, 2014). The antifungal properties of garlic essential oil have been showed in several studies against A. pasasiticus, A. niger, Penicillium cyclopium, Fusarium oxysporum, Penicillium funiculosum and Alternaria tenuissima (Gowda et al, 2004;Li et al, 2014;Muy-Rangel et al, 2017). In addition, Gowda et al (2004) previously reported that garlic essential oil reduced aflatoxin production in mixed feed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tween ® 80 was used as a surfactant in this study due to its low irritation, low toxicity, and high stability, and also because it does not have a fungitoxic effect against Alternaria spp. [18] and others when used at concentrations of 1% to 3% (v•v −1 ) [19,20].…”
Section: Inhibition Of Alternaria Alternata Fungus In Vitromentioning
confidence: 99%
“…After the incubation times, the cellophane membranes containing mycelium were removed to calculate the fungal biomass by weight difference, using a convection air oven at 105 • C for 2 h. The dry weight was expressed in mg box −1 [19]. The dried mycelium was triturated with 10 mL of ethyl acetate to extract cinnabarin in a 500 mL Erlenmeyer flask to a final volume of 50 mL.…”
Section: Production and Synthesis Of Cinnabarin From Pycnoporus Sangu...mentioning
confidence: 99%